2011
DOI: 10.1007/s12192-010-0251-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance and heat shock response in the cold-stenothermal chironomid (NE Italy)

Abstract: To better understand the physiological capability of cold-stenothermal organisms to survive high-temperature stress, we analyzed the thermotolerance limits and the expression level of hsp70 genes under temperature stress in the alpine midge Pseudodiamesa branickii (Diptera Chironomidae). A lethal temperature (LT(100)) of 36°C and a lethal temperature 50% (LT(50)) of 32.2°C were found for the cold-stenothermal larvae after short-term shocks (1 h). Additional experiments revealed that the duration of the exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 34 publications
(51 reference statements)
2
30
0
Order By: Relevance
“…Quite a different type of HSR was observed in other Chironomidae species. The transcription of hsp70 was investigated in the larvae of another Diamesinae representative, Pseudodiamesa branickii (Nowicki, 1873) (Bernab o et al, 2011) and in two members of the subfamily Chironominae, Chironomus tentans Fabricius, 1805 and Chironomus yoshimatsui Martin et Sublette, 1972 (Yoshimi et al, 2009). All of these species displayed a low hsp70 mRNA level at normal temperatures that was strongly induced by HS and a pattern of hsp70 mRNA synthesis that resembles the pattern observed in Stratiomyidae and Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Quite a different type of HSR was observed in other Chironomidae species. The transcription of hsp70 was investigated in the larvae of another Diamesinae representative, Pseudodiamesa branickii (Nowicki, 1873) (Bernab o et al, 2011) and in two members of the subfamily Chironominae, Chironomus tentans Fabricius, 1805 and Chironomus yoshimatsui Martin et Sublette, 1972 (Yoshimi et al, 2009). All of these species displayed a low hsp70 mRNA level at normal temperatures that was strongly induced by HS and a pattern of hsp70 mRNA synthesis that resembles the pattern observed in Stratiomyidae and Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Young (1st and 2nd instar) and mature (3rd and 4th instar) larvae of the cold‐stenothermal Diamesinae P. branickii were used in this study. Our previous studies on this species highlighted that mature larvae are thermotolerant (LT 50 = 32.2 °C, LT 100 = 36 °C) (Bernabò et al ., ) and moderately freezing tolerant (SCP = ‐6.37 ± 0.23 °C, LLT 50 = ‐9.14 ± 1.21 °C, LLT 100 = ‐16.20 °C) (Lencioni et al ., ), with an oxyregulatory behavior (critical limit pressure = 33.6% sat. ; initial decrease of oxygen saturation = 41.9%; slope ratio in piecewise linear regression = 2.8, respiration at 25% saturation = 42.7%) (Lencioni et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…the synthesis of most proteins is retarded, but a group of highly conserved proteins known as heat shock proteins (HSPs) are rapidly synthesized [15]. As molecular chaperones, HSPs perform important functions in the folding/unfolding and translocation of proteins as well as in the assembly/disassembly of protein complexes [16]. Ivanina et al reported HSP60 and HSP70 protein levels increased significantly in Cd-exposed gill cells [17].…”
Section: Introductionmentioning
confidence: 99%